EFEKTIFITAS POSISI PERSALINAN Mc.ROBERT DAN POSISI LITHOTOMI PADA PROSES PERSALINAN KALA II PADA PRIMIPARA DI RSU BANYUMAS TAHUN 2009 - Utami, Soeri; Fajarsari, Dyah (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2011)
There is several delivery position that can be applied in second phase of delivery such as lithotomy, dorsal recumbent, lateral position and squat position. Those position delivery solely purpose for mother´s comfort and shortening of the delivery phase.  Lithotomy position is still a preffered position in the delivery process.  However in shoulder distosion the Mc.Robert position is believed to shorten the 2nd phase of delivery.To know the efectiving of Mc.Robert position and lithotomy position in second phase of delivery for primipara in RSU Banyumas in 2009.This research´s using quasi experimental design by comparing the time duration for second delivery phase for efektifitivy.  The population of the study was all primipara in second delivery phase in RSU Banyumas maternal ward.  Sample sich 60 people divided in to 2 groups, 30 mother´s using lithotomy and the other 30 using Mc.Robert´s position. The everage of 2nd phase time in lithotomy was 44,9 minute and Mc.Robert´s position average time was 33,3 minute.  There was significant difference  for 2nd delivery phase time using lithotomy compare to Mc.Robert´s position (Mc.Robert´s 33,33±SD 8,74 minute, lithotomy 44,9±SD 9,96 minute´s).  Shortened by 11,57 minutes in this study, Mc.Robert´s position in second phase more effective than lithotomy´s positions in second phase of delivery for primipara with p = 0,000 Keyword : Second delivery phase Mc.Robert´s position, Lithotomy´s position, primipara